Evaluation of Polycyclic Aromatic Hydrocarbon Pollution From the HMS Royal Oak Shipwreck and Effects on Sediment Microbial Community Structure - Thomas, Gareth E.; Bolam, Stefan G.; Brant, Jan L.; Brash, Rodney; Goodsir, Freya; Hynes, Clare; McGenity, Terry J.; McIlwaine, Paul S. O.; McKew, Boyd A. (Frontiers in Marine Science, 2021)
Given many shipwrecks contain oil products there is a paucity of studies investigating the status of shipwrecks and their surrounding environments. This study evaluates any potential effect the World War II shipwreck HMS Royal Oak is having on surrounding benthic sediments in Scapa Flow, Scotland. HMS (Her Majesty’s Ship) Royal Oak sank in 1939, subsequently leaked oil in the 1960s and 1990s, and is estimated to still hold 697 tonnes of fuel oil. In this study, sediments were analysed, over a 17.5 cm depth profile, along a 50 – 950 m cruciform transect away from the shipwreck. Analysis of polycyclic aromatic hydrocarbons (PAHs) revealed low concentrations (205.91 ± 50.15 µg kg-1 of dry sediment), which did not significantly differ with either distance from the shipwreck nor sediment depth. PAH concentrations were well below the Effects-Range Low for the OSPAR (Oslo/Paris convention for the Protection of the Marine Environment of the North-East Atlantic) maritime area. The average Pyrogenic Index, in sediments around HMS Royal Oak, was 1.06 (± 0.34), indicating PAHs were pyrogenic rather than petrogenic. Moreover, analysis of sediment microbiomes revealed no significant differences in bacterial community structure with distance from the shipwreck, with extremely low levels of obligate hydrocarbonoclastic bacteria (OHCB; 0.21% ± 0.54%). Both lines of evidence suggest, at the time of sampling, sampled sediments are not currently being impacted by petrogenic hydrocarbons and show no long-term impact by previous oil-spills from HMS Royal Oak.